Malaysia as the Archetypal Garden in the British Creative Imagination - Ahmad, Siti Nuraishah (Center for Southeast Asian Studies, Kyoto University, 2014)
European travel writing (1512–1984) represented Malaysia as a tropical Garden of Eden, an image that has also percolated into literary texts concerning the region. This article examines spatial images in British fiction through the framework of archetypal literary criticism and theories of colonial representations of space to reveal the worlding (Spivak 1999) of Malaysia as a garden. In order to ascertain the ways in which the garden archetype has been deployed by the British creative imagination in the past and the present, novels from the colonial and postcolonial periods have been selected for analysis. Three dominant incarnations of the garden archetype can be discerned throughout novels by Joseph Conrad, W. Somerset Maugham, and Anthony Burgess: the lush, Romantic garden; the restrained, disciplined Victorian garden; and the barren, dried-up garden. The postcolonial British novel, for its part, deploys images of the barren garden revived (William Riviere’s Borneo Fire) as well as a return to the earlier Conradian image of the Romantic locus amoenus (Frederick Lees’ Fool’s Gold). This article concludes that the representation of Malaysia in various guises of the archetypal garden negates the indigenous worldview concerning space and produces instead “knowledge” about Malaysia rooted in the white man’s perspective